Emotions in Nursing Care Prioritisation Decisions: A Critical Incident Debriefing Study of Missed Nursing Care. - Cohen, Mirit; Massalha, Yosur; Drach‐Zahavy, Anat; Srulovici, Einav (Journal of Advanced Nursing (John Wiley & Sons, Inc.), 2026)
Aim: To examine the decision‐making processes underlying missed nursing care. Design: A qualitative study using Critical Incident Debriefing interviews. Methods: Fifteen nurses from inpatient wards in a general hospital participated in semi‐structured interviews following their morning shifts. Interviews focused on care prioritisation incidents leading to missed nursing care. Data were analysed using thematic analysis. Results: Analysis revealed a central theme of emotions as crucial determinants in care prioritisation decisions. Two subthemes emerged: emotions as drivers of care prioritisation decisions and emotions as responses to these decisions. Positive emotions motivated nurses to prioritise care for specific patients, while negative emotions sometimes led to care delays. Successful care completion generated professional satisfaction, while care omissions produced complex emotional responses, including guilt, frustration and helplessness. Conclusion: The dual emotional processes identified in this study—emotions functioning as both drivers and responses in care decisions—challenge purely structural explanations of missed nursing care. This perspective reframes nurses as emotionally engaged decision‐makers who actively navigate care priorities rather than passively react to contextual constraints, offering a more comprehensive framework for understanding the complexity of clinical judgement in real‐world settings. Implications for the Profession and/or Patient Care: This study positions emotions as legitimate components of clinical decision‐making rather than cognitive biases. For nursing practice, this necessitates integrating emotional awareness into professional development. For patient care, recognising emotional underpinnings may promote equitable care distribution through interventions that engage with the emotional realities of nursing work. Impact: This study addressed limited understanding of decision‐making in missed nursing care, particularly emotions' role. Findings reveal how emotions influence nurses' prioritisation decisions and wellbeing, with implications for nurses, educators and administrators seeking interventions addressing structural and emotional dimensions. Reporting Method: This study adhered to the Standards for Reporting Qualitative Research (SRQR) guidelines (Appendix S1). Patient or Public Contribution: No patient or public contribution.